Treatment results of methotrexate and folinic acid as primary chemotherapy for nonmetastatic gestational trophoblastic neoplasia - Srisomboon J. (2014)
Objective: To evaluate the efficacy and toxicity of methotrexate and folinic acid (MTX-FA) chemotherapy in patients with nonmetastatic gestational trophoblastic neoplasia (NMGTN) Material and Method: Between 1997 and 2003, a total of 67 patients with NMGTN received treatment at the Chiang Mai University Hospital. Of the 67 patients, 55 were initially treated with methotrexate 1.0 mg/kg intramuscularly (IM) on day 1,3,5, and 7 and folinic acid 0.1 mg/kg IM on day 2,4,6 and 8. Treatment courses were repeated every 14 days. Clinical characteristics and outcomes were analyzed. Results: All 55 patients with NMGTN were cured. Of the 55 patients initially treated with MTX-FA, 49 (89%) achieved complete remission. Six (11%) patients developed methotrexate resistance, 3 were cured with actinomycin D, 1 were cured with 5-fluorouracil followed by etoposide, 2 required hystertectomy to attain remission. No serious toxicity was noted. Conclusion: Methotrexate and folinic acid chemotherapy is highly effective and well-tolerated in treating patients with nonmetastatic gestational trophoblastic neoplasia.